Kepatuhan Perawat terhadap Enam Langkah Cuci Tangan - Manullang, Netty Grace; Hutapea, Lyna M. N. (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine nurses' compliance with the six steps for washing hands in the medical surgical room in the Cihampelas Building, Bandung Adventist Hospital. This research method uses quantitative research with descriptive analysis by observing nurses washing their hands. This research showed that 98.7% of nurses had complied with the six steps for hand washing, and 0.4% had yet to. The study concludes that nurses who abide by the six steps of hand washing are good, but some still need to comply with the six steps. It is recommended that nurses continue carrying out the six steps for washing hands and assess factors influencing compliance. Keywords: Washing Hands, Six Steps